- #1
enigmatic01
- 8
- 1
- Homework Statement
- Use the formal definition of Big-Oh to prove that if f (n) and g(n) are nonnegative functions such that f (n) = O(g(n)), f (n) + g(n) = Ω(g(n))
- Relevant Equations
- ...
Use the formal definition of Big-Oh to prove that if f (n) and g(n) are nonnegative functions such that f (n) = O(g(n)), f (n) + g(n) = Ω(g(n)).
By the definition of Big-Oh:
If f(n) and g(n) are non-negative functions such that f(n) = O(g(n)) there must be positive constants c and n0 such that 0 ≤ f(n) ≤ c(g(n)) for all n ≥ n0
Would this be correct:
If 0 ≤ f(n) ≤ c(g(n)) and f(n) and g(n) are non-negative functions we know g(n) ≤ ( f(n) + g(n) ).
Since g(n) ≤ f(n) + g(n) there must be a constant c, namely 0 < c ≤ 1, such that c(g(n) ≤ g(n). We could then say 0 ≤ c(g(n)) ≤ f(n) + g(n) which is the definition of f (n) + g(n) = Ω(g(n))
By the definition of Big-Oh:
If f(n) and g(n) are non-negative functions such that f(n) = O(g(n)) there must be positive constants c and n0 such that 0 ≤ f(n) ≤ c(g(n)) for all n ≥ n0
Would this be correct:
If 0 ≤ f(n) ≤ c(g(n)) and f(n) and g(n) are non-negative functions we know g(n) ≤ ( f(n) + g(n) ).
Since g(n) ≤ f(n) + g(n) there must be a constant c, namely 0 < c ≤ 1, such that c(g(n) ≤ g(n). We could then say 0 ≤ c(g(n)) ≤ f(n) + g(n) which is the definition of f (n) + g(n) = Ω(g(n))